Implementation of Online Learning System When Covid-19 in The Republic of Tatarstan, Russia - Refly Setiawan; Ida Farida (ENTITA: Jurnal Pendidikan Ilmu Pengetahuan Sosial dan Ilmu-Ilmu Sosial, 2021)
Abstract: The implementation of the online learning system is one of the right steps taken by the Government of the Republic of Tatarstan in preventing the spread of the Covid-19 virus in the territory of the Republic of Tatarstan. This study aims to describe the implementation of online learning when the Covid-19 outbreak in the Republic of Tatarsatan and to find out how students' satisfaction and motivation to learn by implementing the online learning system. The research method used in this study is a descriptive method with a qualitative approach. Data collection is done through interviews, documentation, and observation with data collection tools that have been prepared. The location in this study in the Republic of Tatarstan is precisely at Kazan Federal University. The results showed that the implementation of online learning systems in the Republic of Tatarstan especially at Kazan Federal University had not been fully effective. That is because there are still many student complaints about using online learning applications such as Microsoft teams in learning activities at Kazan Federal University and most students do not fully understand the material delivered by lecturers in online learning. Keywords: Online Learning System, Covid-19, Republic of Tatarstan